PERBANDINGAN KADAR ENZIM ALKALINE PHOSPHATASE (ALP) PADA SERUM HEMOLISIS RINGAN DAN NON HEMOLISIS - Tria Agustina; Bastian Bastian; Dewi Hartati (Poltekkes Kemenkes Jambi, 2023)
Background: Alkaline Phosphatase (ALP) is a hydrolase enzyme that is first produced by the liver epithelium and osteoblasts (cells that form new bone), this enzyme is mostly found in the liver and bones. ALP enzyme examination can be affected if there is damage to the cells, causing haemolysis. Haemolysis can be affected by phlebotomy techniques at an inappropriate pre-analytical stage, so that haemolysis can cause increased concentrations in red blood cells compared to serum or plasma, thus giving false concentration results. This study aims to determine the differences in ALP enzyme levels in mild haemolysed serum and non-haemolysed serum. Methods: The study population included all 17 male students of DIV Medical Technology Laboratory, Faculty of Science and Technology Muhammadiyah Palembang, by differentiating inclusion, namely aged 17 to 22 years, male sex and willing to be respondents. Samples in the form of mild hemolysis and non-hemolysis serum were taken from the respondents. The stages of the research began with taking venous blood samples, processing the blood into non-hemolytic serum and mild hemolytic serum, and ALP examination using the Biosystem BA 200 tool. Results: This study showed that the difference between ALP enzyme levels in non-haemolytic and haemolytic samples was 73.9 U/L or 55%. The data analysis test used the Paired T test which obtained p ≥ 0,000. Conclusion: There are differences in results between mild haemolysed serum and non-haemolysed serum.